METTL3 inhibits inflammation of retinal pigment epithelium cells by regulating NR2F1 in an m6A-dependent manner - Meng, Jiayu; Liu, Xianyang; Tang, Shiyun; Liu, Yusen; Zhao, Chenyang; Zhou, Qian; Li, Na; Hou, Shengping (Frontiers in Immunology, 2022)
N6-methyladenosine (m6A) RNA methylation has been proven to be involved in diverse biological processes, but its potential roles in the development of lipopolysaccharide (LPS) induced retinal pigment epithelium (RPE) inflammation have not been revealed. In this study, we explored the effects and underlying mechanisms of methyltransferase-like 3 (METTL3) in LPS stimulated RPE cells. Proliferation of METTL3-silenced RPE cells was examined by Cell counting kit-8 (CCK8) and 5-Ethynyl-2´-Deoxyuridine (Edu). Expression of tight junction proteins ZO-1 and Occludin, and secretion of inflammatory factors interleukins (IL)-1, 6 and 8 were detected by Western blotting or Enzyme-linked immunosorbent assay (ELISA). RNA sequencing and methylated RNA immunoprecipitation (MeRIP) sequencing were used to analyze the target gene nuclear receptor subfamily 2 group F member 1 (NR2F1) of METTL3. Our results showed that both human RPE (hRPE) cells and ARPE19 cells exhibited inhibited proliferation, tight junction protein expression, and increased inflammatory factor secretion after METTL3 silencing. Mechanistically, we found that NR2F1, as a METTL3-methylated target gene, inhibits Occludin level and promotes IL-6 secretion of RPE cells in an m6A-dependent manner. Interestingly, NR2F1 deficiency reversed the decreased Occludin expression and increased IL-6 secretion in METTL3-defective RPE cells. In conclusion, our study revealed that METTL3 attenuates RPE cell inflammation by methylating NR2F1, suggesting the critical role of METTL3 in RPE cells.